Multimodal Feedback Workshop for English Teachers in Designing Questions Based on Higher Order Thinking Skill - Syafryadin Syafryadin; Dian Eka Chandra Wardhana; Annisa Astrid (STAI Hubbulwathan Duri, 2022)
This study aimed to determine whether or not there is quality improvement of HOTS-based questions through multimodal feedback made by English teachers. Besides, this study intended to find out the forms of feedback given during the implementation of multimodal feedback and English teachers' perception of multimodal feedback in designing HOTS-based English questions workshops. This study used a mixed-method involving 30 English teachers willing to participate in the training. Furthermore, research data collection was done through the provision of tests, interviews, and observations. Several experts have validated the instruments used in this study. The data were analyzed quantitatively and qualitatively. Quantitative data were analyzed using SPSS, while qualitative data in interviews and observation sheets were analyzed using several stages, including data reduction, data display, and concluding. The results of this study indicated a quality improvement of HOTS-based English questions that have been made by English teachers, which was evidenced by an increase in the results from pretest to posttest. The next finding is that three types of feedback helped teachers make HOTS-based English questions through multimodal feedback: peer feedback, oral conference, and written feedback. Another finding was that English teachers gave a positive perception towards designing HOTS-based English questions through multimodal feedback because these activities provided positive input on their ability to make HOTS-based English questions. In conclusion, the findings of this study benefit English teachers in designing HOTS-based questions, so that teachers can implement the result of the workshop in the teaching and learning process.